PCR based unraveling of the cryptic epizootiology of bubaline theileriosis targeting the merozoite surface antigen gene - SUDAN, VIKRANT; JAISWAL, AMIT KUMAR; PARASHAR, RAHUL; SHANKER, DAYA (The Indian Journal of Animal Sciences, 2016)
Lower parasitemia often skips the conventional microscopic and serological techniques from detecting latent, cryptic and chronic carrier states of bovine tropical theileriosis infection in buffalo hosts. A PCR was laboratory standardized and later validated on 80 field samples of suspected bubaline (Bubalis bubalis) hosts. Oligonucleotide primers (TBR F/R), selected from the gene encoding the 30-kDa major Theileria annulata merozoite surface antigen were custom designed and used for PCR amplifications. The sensitivity and specificity of PCR in relation to blood smear was compared based on kappa value predictions. Keeping blood smear examination as a gold standard for detecting actual number of confirmed positive cases, PCR on blood was 100 % sensitive and 88.6 % specific. The described PCR-based assay provides a valuable tool to study the epidemiology of bovine tropical theileriosis (BTT) in buffaloes and some vital data regarding epidemiology of theileriosis in water buffaloes from semi arid parts of India was generated.